PELATIHAN PUBLIC SPEAKING di RPTRA AMANAH BUNDA UPAYA MENINGKATKAN KEPERCAYAAN DIRI SEJAK DINI - Salman , Doddy; Hananti , Gishenova Sabrina; Nur Wulan; Garrison , Dennis; Alfred Pradipta; Dwinanda , Devina Adilah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Public Speaking or what is more commonly called public speaking skills is one of the skills that must be possessed in today's global era. Public speaking (public speaking skill) is the ability to speak in front of many people, both in closed and open spaces. In an effort to improve communication skills, public speaking skills are one of the soft skills that children need to have (Turistiati, 2019). This is also a challenge for the Child-Friendly Integrated Public Spaces of Amanah Bunda in Tanjung Duren. Therefore, this skill must be prepared, nurtured, and developed from an early age. For children who are used to expressing opinions, they are able to express and develop their potential from an early age and this can become a skill that will help them in the future. Public Speaking skills are really needed by students because they can help students with presentations and organizational skills. Therefore, Public Speaking must be trained and instilled in children as early as possible